Increased visceral fat area to skeletal muscle mass ratio is positively associated with the risk of cardiometabolic diseases in a Chinese natural population: A cross‐sectional study. Issue 2 (2nd December 2022) - Zhang, Shi; Huang, Yaping; Li, Jing; Wang, Xincheng; Wang, Xiaohe; Zhang, Minying; Zhang, Yanju; Du, Meiyang; Lin, Jingna; Li, Chunjun
Abstract: Aims: Visceral adiposity and skeletal muscle loss may be positively correlated with cardiometabolic outcomes. This study aimed to explore the associations between the visceral fat area to skeletal muscle mass ratio (VSR) and the risk of cardiometabolic diseases in a Chinese natural population. Materials and Methods: A total of 5158 participants were included in this study. Body composition, anthropometrical, and biochemical measurements were performed. Body composition was assessed via the direct segmental multi‐frequency bioelectrical impedance analysis method. The associations between VSR and metabolic associated fatty liver disease (MAFLD), hyperglycemia, hypertension, dyslipidemia, and hyperuricemia were analysed. Results: With the increase of VSR by one quartile, the odds ratio (OR) increased significantly for all five cardiometabolic diseases in both genders ( p trend < 0.001). With regard to the highest versus the lowest quartile of VSR, the ORs for cardiometabolic diseases were significantly higher in women than in men. Restricted cubic splines showed that there were significant non‐linear relationships between VSR and the risk of MAFLD, dyslipidemia, hyperglycemia, and hypertension in both genders ( p for non‐linearity <0.05). The risk was relatively flat until VSR reached 3.078 cm 2 /kg in men and 4.750 cm 2 /kg in women and started to increase rapidly afterwards. In men, however, the risk slowed down after the VSR value reached around 4 cm 2 /kg. Conclusions: VSR was positively associated with cardiometabolic diseases regardless of gender. As VSR increased, the risk of cardiometabolic diseases was significantly higher in women than in men. Trial Registration: www.chictr.org.cn (Registration number: ChiCTR2100044305).